Effect of κ-Carrageenan on the Microstructure and Properties of Beeswax-Based Emulsion Gels - SUN Yahui, HAN Lijuan, SU Lingzhi, CHANG Mengdi, ZHANG Shiqi, ZHAO Zhouqiao, HE Junbo, QI Yutang, ZHAO Lei (Shipin Kexue, 2023)
Emulsion gels (EG) and bigels (BG) were prepared by high-speed shear treatment of a mixture of beewax oleogels with pure water or κ-carrageenan hydrogel in the absence of emulsifiers, respectively. The effect of κ-carrageenan on the microstructure, physical stability, water- and oil-binding capacity, hardness, rheology and thermal properties of EG with different mass fractions of oleogel (40%, 60% and 80%) was investigated. The results showed that EG and BG were water-in-oil (W/O) type. Compared with EG, the addition of κ-carrageenan did not change the beeswax crystal type, oil-binding capacity or thermal properties of BG, but could improve the plasticity, water-binding capacity, physical stability, hardness and viscoelasticity of BG. In addition, with an increase in oleogel concentration in BG, the average size and size distribution range of dispersed aqueous droplets became smaller and narrower, and the shear resistance improved gradually.